What's That?Big Machine - Worsley,Belinda (London Ladybird, 2016)
The Ladybird First Words and Pictures series is perfect for helping to develop your toddler's early vocabulary. For older children, linking words to pictures is also an important first reading skill. What's that? Big Machines contains clear, bright vehicle pictures and words to look at and talk about, perfect for young children curious about the world around them.
Keywords: English vocabulary book